2012
DOI: 10.1680/cien.11.00046
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure resilience for high-impact low-chance risks

Abstract: Infrastructure resilience is the ability of an infrastructure system to withstand or recover quickly from difficult conditions, which in turn requires a detailed understanding of vulnerability and risk. But while designing for foreseeable risks is a challenge, accounting for risks that are difficult or even impossible to foresee – such as those arising from complex interdependent processes – poses a far greater challenge. This paper argues that civil engineers need a way of addressing such low-chance but poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 6 publications
0
29
0
1
Order By: Relevance
“…Failure here means service disruptions, and thus, these studies tend to focus on maintaining system function or system recovery practices. This characterization of safe-to-fail includes risk analysis and critical infrastructure security studies that emphasize awareness of unforeseen risks (Blockley et al, 2012;Boin & McConnell, 2007). This characterization of safe-to-fail includes risk analysis and critical infrastructure security studies that emphasize awareness of unforeseen risks (Blockley et al, 2012;Boin & McConnell, 2007).…”
Section: 1029/2019ef001208mentioning
confidence: 99%
See 1 more Smart Citation
“…Failure here means service disruptions, and thus, these studies tend to focus on maintaining system function or system recovery practices. This characterization of safe-to-fail includes risk analysis and critical infrastructure security studies that emphasize awareness of unforeseen risks (Blockley et al, 2012;Boin & McConnell, 2007). This characterization of safe-to-fail includes risk analysis and critical infrastructure security studies that emphasize awareness of unforeseen risks (Blockley et al, 2012;Boin & McConnell, 2007).…”
Section: 1029/2019ef001208mentioning
confidence: 99%
“…This characterization of safe-to-fail includes risk analysis and critical infrastructure security studies that emphasize awareness of unforeseen risks (Blockley et al, 2012;Boin & McConnell, 2007). Another study calls on engineers to recognize the "low-chance but potentially high-impact" risks arising from interdependencies of complex infrastructure where the system behavior may not be fully understood and to design the system as robust to unforeseen risks (Blockley et al, 2012). Another study calls on engineers to recognize the "low-chance but potentially high-impact" risks arising from interdependencies of complex infrastructure where the system behavior may not be fully understood and to design the system as robust to unforeseen risks (Blockley et al, 2012).…”
Section: 1029/2019ef001208mentioning
confidence: 99%
“…The primary examples are the risk and reliability studies since Freudenthal (1947) suggested the idea (see ICOSSAR conferences at Benjamin and Cornell 1970;Blockley 1980Blockley , 2008Melchers 1999;Ditlevsen and Madsen 2007;IASSAR 2014). Other examples are (Blockley, Agarwal, and Godfrey 2012) the vulnerability of systems to low-chance but high-consequence risks and robustness as the property of being strong, healthy, hardy and able 'to take a knock'. The latter is not easily mathematised and has been covered, since 1970 after the Ronan Point collapse in 1968, by codified rules in amendments to the UK Building Regulations and in more recent standards (BSI 2006) to inhibit progressive collapse.…”
Section: Resiliencementioning
confidence: 99%
“…The considerable effort in risk and reliability analysis is a primary example with its partial focus on parameter uncertainty and inadequate recognition and treatment of system (modelling) and human uncertainty (Blockley 1992b) and the consequent reluctant uptake within the community of practitioners ( Figure 1). Blockley, Agarwal, and Godfrey (2012) have discussed the relationships between these modern criteria. For example, resilience must entail or imply robustness and hence robustness is necessary but not sufficient for resilience, since the latter also includes recovery to an original state or to a state which continues to meet an acceptable level of the original purpose of the system.…”
Section: Resiliencementioning
confidence: 99%
“…According to Blockley et al (2012), infrastructure resilience is the ability of an infrastructure system to withstand or recover quickly from difficult conditions. It is not a simple property like a safety factor or probability of failure and it is linked to vulnerability and robustness, as follows.…”
mentioning
confidence: 99%